Poetry in space [videorecording] - Bernaldez, Reina Marie C.; Java, Melva Rodriguez; Villoria, Leon C.; Philippines. National Commission for Culture and the Arts.; University of San Carlos (Cebu). ([Manila NCCA], 1997)
A documentation of the history of architecture of houses, churches, cemeteries and other structure from the Spanish colonial period to the present in the Visayas especially those in Cebu and Iloilo.
VHS.
Narrators, Melva Rodriguez Java, Rod Salazar.
Keywords: Architectur,Domestic -- Philippines -- Carcar(Cebu); Architecture, Colonial -- Philippines -- Iloilo; Architecture, Domestic -- Architecture, Colonial -- Philippines -- Iloilo. -- Philippines -- Carcar (Cebu); Cemeteries -- Philippines -- Iloilo; Churches -- Philippines -- Cebu; Churches -- Philippines -- Iloilo; Dwellings -- Philippines -- Carcar (Cebu); Dwellings -- Philippines -- Iloilo; Stone house -- Philippines -- Carcar (Cebu); Stone house -- Philippines -- Iloilo